The prohibition of sincere confession as an ineffective criminal policy in the crime of femicide - Marín Sandoval, Rocío Angélica (2024)
The interest of this article arises from the ineffectiveness of the criminal policy used by the Peruvian State in order to reduce the high rate of the crime of feminicide, specifically, that which prohibits the application of the reduction of the penalty for sincere confession. In this line of ideas, what is intended through this article is that the application of this figure of the Criminal Prize Law is allowed in the crime of feminicide, today that offers various advantages not only for the accused in the reduction of his sentence, but also which also promotes timely justice, reduces economic expenses for all procedural parties as well as for the State. Therefore, in the course of the investigation, the criminal political foundations that justify the application of the sincere confession in the crime of feminicide will be provided.